Nonlocal dilaton coupling to dark matter: cosmic acceleration and pressure backreaction - Amendola, Luca; Gasperini, Maurizio; Ungarelli, Carlo (Physical review. D, Particles, fields, gravitation, and cosmology, 2008)
A model of nonlocal dilaton interactions, motivated by string duality symmetries, is applied to a scenario of “coupled quintessence” in which the dilaton dark energy is nonlocally coupled to the dark-matter sources. It is shown that the nonlocal effects tend to generate a backreaction which—for strong enough coupling—can automatically compensate the acceleration due to the negative pressure of the dilaton potential, thus asymptotically restoring the standard (dust-dominated) decelerated regime. This result is illustrated by analytical computations and numerical examples.